Penerapan Metode Drill untuk Meningkatkan Kreatifitas dan Hasil Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Sosial - Ni Komang Murtini (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this research is to find out whether drill methods can improve students' creativity and learning outcomes in social science subjects and find out how the implementation of drill methods can improve students' creativity and learning outcomes on materials maintaining the natural and artificial environment in social science subjects’ grade 3 State Elementary School 11 Cakranegara. The method used in this study is class action research. In this study, the action of improving the learning process was carried out in two cycles. The study was conducted during two face-to-face classes. From the results of class action research that has been implemented it can be concluded that: (1) The application of drill methods can increase creativity, activities, student learning outcomes and student completion in materials maintaining the natural and artificial environment in students of 3rd grade of State Elementary School 11 Cakranegara. The average grade of student learning outcomes also increased in cycle I and cycle II which were 68.79 and 75.31; (2) Implementation of drill methods in order to overcome student learning difficulties is carried out every time the teaching and learning process. The form of drill they get is to read the questions and write them, even to be more effectively given to them home tasks such as answering the question with better writing. Then to memorize is done pre-tech in front of the class at the next meeting and so on.